Program Pekarangan Pangan Lestari (P2l) Di Kelompok Wanita Tani (Kwt) Walidah Desa Sukaresmi Kecamatan Cisaat Kabupaten Sukabumi - M. Anwar Mukhlis; Reny Sukmawani; Ema Hilma Meilani (Universitas Muhammadiyah Sukabumi, 2022)
KWT Walidah Sukaresmi Village, Cisaat District, Sukabumi Regency is one of the KWTs that is running the Sustainable Food Garden (P2L) program starting in 2020. Its activities are carried out using an empowerment method that involves the active participation of all members under the assistance of local agricultural extension workers. The results of the activity show that KWT Walidah can carry out activities in accordance with the provisions set by the Food Security Agency. Meanwhile, based on the evaluation results, it is shown that from the aspect of availability, accessibility, utilization and income, it is in good category. Based on this, the P2L program should continue to be carried out sustainably by KWT Walidah in order to support food security at the family level.